Slanted 42 : books. - Harmsen, Lars (Karlsruhe : Slanted, 2023)
Slanted #42—BOOKS is an issue about books. Every day we wonder if the future of the (printed) book is tied to its sensual quality? How can beautiful books secure their place in the media and society? How are content, medium, and form connected? Is manufacturing and design quality, in addition to its functionality, just to be understood as a marketing argument? In this issue Slanted presents experimental design strategies—books that go unconventional ways—in contrast to classical books. They are looking for accidents, work that is based on mistakes and inaccuracy, cutting edge approaches, as well as new experimental procedures, from processing to AI-generated content. In opposition, it presents timeless book designs, where content dictates form.
01 Maximize the possibilities -- 02 Functional use of reading -- 03 Ordinary disruption -- 04 Wispy and fragile -- 05 Visually tactile texture -- 06 Wordless tangible -- 07 Purely Typography -- 08 Whatever happens with AI -- Essays: Ian Lyman, Demian Conrad, Matt Lamont, Birgit Schmitz, Pata-No PUN LTD, Dermot Mac Cormack, Lars Harmsen
boek